Neuroprotection by PIGF gene-modified human mesenchymal stem cells after cerebral ischaemia - Liu, H. (2006)
Intravenous delivery of mesenchymal stem cells (MSCs) prepared from adult bone marrow reduces infarction size and ameliorates functional deficits in rat cerebral ischaemia models. Placental growth factor (PIGF) is angiogenic to impaired non-neural tissue. To test the hypothesis that PIGF contributes to the therapeutic benefits of MSC delivery in cerebral ischaemia, we compared the efficacy of systemic delivery of human MSCs (hMSCs) and hMSCs transfected with a fibre-mutant F/RGD adenovirus vector with a PIGF gene (PIGF-hMSCs). A permanent middle cerebral artery occlusion (MCAO) was induced by intraluminal vascular occlusion with a microfilament. hMSCs and PIGF-hMSCs were intravenously injected into the rats 3 h after MCAO. Lesion size was assessed at 3 and 6 h, and 1, 3, 4 and 7 days using MR imaging and histology. Functional outcome was assessed using the limb placement test and the treadmill stress test. Both hMSCs and PIGF-hMSCs reduced lesion volume, induced angiogenesis and elicited functional improvement compared with the control sham group, but the effect was greater in the PIGF-hMSC group. Enzyme-linked immunosorbent assay of the infarcted hemisphere revealed an increase in PIGF in both hMSC groups, but a greater increase in the PIGF-hMSC group. These data support the hypothesis that PIGF contributes to neuroprotection and angiogenesis in cerebral ischaemia, and cellular delivery of PIGF to the brain can be achieved by intravenous delivery of hMSCs.